(untitled) (Dhaka University Journal of Science, 2019)
In this paper we estimate European put option price by using awell-established option pricing model, namely, the Constant Elasticity of Variance (CEV) model for the elasticity parameter β< 2 and then compare it with the benchmark Black-Scholes (BS) model. We calculate the Greeks under the CEV model for β=0,1 and 1.95 and compare them with that of the B-S one. Finally, we investigate the put price and Greeks values for at-the-money (ATM), in-the-money (ITM) and out-of-the-money (OTM) situations. Dhaka Univ. J. Sci. 67(2): 105-110, 2019 (July)